Characterization of the Alcohol Use Disroder : A cross-cultural bio-psycho-social approach in France, Benin and Togo - (:unkn) unknown (My University, 2023)
Alcohol has detrimental effects on health, leading to significant morbidity as well as economic and social consequences. Disorders related to its consumption rank among the leading causes of disability worldwide. However, epidemiological data on Alcohol Use Disorder (AUD) in sub-Saharan Africa remains scarce. This thesis aims to characterize AUD in France, Benin, and Togo to optimize prevention and treatment strategies. Initially, a systematic review found that only 16 studies have been conducted in the general African population, none of which used the DSM-5 criteria. The prevalence in this region ranges from 0.1% to 33.2%, highlighting a major public health issue. Subsequently, a survey using DSM-5 criteria was conducted in the general populations of Togo and Benin. In Togo, the AUD prevalence was 12.4% (CI 95%: 9.5-15.7) and 8.7% in Benin (CI 95%: 6.4-11.7). The primary comorbidities in Togo are suicidal risk, depression, gambling addiction, and smoking, with male gender and certain scores as risk factors. In Benin, the main disorders are suicidal risk, smoking, and psychotic syndrome. Lastly, a survey was carried out in hospitals in France, Togo, and Benin. In France, the majority of AUD patients are 50-year-old men, with 82% being smokers. In Benin, they are mostly young Christian men living in urban areas. In Togo, they are men in their forties working in cities. Additionally, a study was conducted to explore variations in BDNF and Pro-BDNF in patients suffering from major depressive episodes and AUD.
Keywords: African Research